SIFAT KUALITATIF, MORFOMETRIK, DAN KARKAS BURUNG AYAMAN (Gallirallus phillippensis) DI KAMPUNG MACUAN DISTRIK MASNI KABUPATEN MANOKWARI - Sada, Yusak Jeckson; Warsono, Irba Unggul; Murwanto, A. Gatot (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2018)
Ayaman bird (Gallirallusphilippensis) usually hunted for meat for people in Prafi, specifically in Macuan village. The aim of this research was to determine the qualitative, morphometric measurement, carcass quality and meat nutritional contain of Ayaman bird. Fifty six head of ayaman birds (28 males and 28 females) was used in this research. Descriptive method with case study technique was used. Data was analyzed with t test. Qualitative trait such as feather color, shank shape were the same between male and female bird except for the color of the beak and shank were different. Male and female beak and wings length were not significantly different, while tail and middle finger of the male were longer than the female bird. Carcass, hind and fore carcassweight were heavier in male than female bird, but carcass percentage were the same between male and female bird. Meat nutritional contain such as protein, fat, energy and cholesterol were the same between male and female bird.